Expression and significance of TOLL2, TARC and MDC in placenta tissue of pregnant patients infected with syphilis: TOLL2, TARC and MDC in placenta tissue - Cao, Juan; Chen, An'er (Cellular and Molecular Biology, 2022)
This study was developed to investigate the expression of TOLL2, TARC and MDC in placenta tissue of pregnant patients infected with syphilis and their clinical significance. For this aim, placenta samples were collected from five pregnant patients co-infected with syphilis and five undergoing full-term delivery before RT-PCR was performed to detect the mRNA expression of TLR2, TARC and MDC genes. The protein expression of TLR2, TARC and MDC genes was examined by Western Blotting. Results showed that TLR2, TARC and MDC were expressed in placental syncytiotrophoblast cells of patients with pregnancy-associated syphilis infection. TLR2 level was found significantly higher in placenta tissue of patients with pregnancy-associated syphilis infection compared with normal placenta tissue (P<0.05), so were TARC (P<0.05) and MDC genes (P<0.05). It is concluded that TOLL2, TARC and MDC levels significantly increased in the placenta tissue of pregnant patients infected with syphilis, suggesting that the three genes were involved in the molecular pathology of the patients.